MODEL COLLABORATIVE GOVERNANCE DALAM IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI INDONESIA: SYSTEMATIC LITERATURE REVIEW DAN RELEVANSINYA BAGI PROVINSI SULAWESI BARAT - Muhammad Ishak Najamuddin; Rahayu Rahayu; Muhammad Irvan Nur’Iva; Herman Herman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
Waste management issues constitute a strategic agenda that requires a collaborative governance approach considering the number of actors involved, limited government capacity, and the importance of community engagement. This study aims to synthesize various collaborative governance models in the implementation of waste management policies in Indonesia and examine their relevance to strengthening waste governance systems in West Sulawesi Province.The research employs a Systematic Literature Review (SLR) method based on the PRISMA protocol on scientific publications from 2010–2026 collected from reputable databases. The selection process resulted in 15 articles that met the inclusion criteria and were analyzed thematically.The findings show that the most widely applied collaboration patterns include Collaborative Governance, Public–Private Partnership (PPP), and Penta-Helix Collaboration. The implementation of these models contributes to improving waste service quality, expanding public participation, increasing funding efficiency, and fostering community-based innovation. Additionally, the government’s role has shifted from a dominant actor to a facilitator and coordinator of cross-stakeholder collaboration. However, collaborative practices still face challenges such as weak institutional coordination, limited resources, sectoral ego, and suboptimal public participation.In the context of West Sulawesi, several governance issues highlight the importance of adopting a more integrated and adaptive collaborative model. Therefore, this study recommends strengthening collaborative regulations, establishing multi-stakeholder forums, optimizing public–private partnerships, empowering communities, and utilizing digital technology as sustainable policy strategies.Keywords: collaborative governance, systematic literature review, public policy, waste management, multi-stakeholder partnership